THE ROLE OF GOOGLE TRANSLATE FOR INDONESIAN EFL LEARNERS - Ni Luh Putu Krisnawati (Proceedings of ISELT FBS Universitas Negeri Padang, 2017)
Teaching English as a foreign language is a difficult and challenging job to do since the ability of learners in receiving the lesson may differ from one to another. A teacher is required to be creative and innovative in designing the syllabus and activity to be conducted in class. One of the ways to teach English is by using Google Translate. As everyone knows that google translate is a tool provided by Google Inc that enables the user to get the meaning of the source language into the target language. Therefore the aims of the study are, (1) to know the advantages and disadvantages in using Google Translate for Indonesian EFL learners, (2) to know what English proficiency skill can be develop by using Google Translate. The respondent of this study are student in the second semester of English Department, Udayana University. This study uses the descriptive qualitative method in describing the finding and a set of questionnaire will be given to the respondent to know their opinion about using Google Translate during their learning process. An observation method is also conducted to know the improvement of the English proficiency made by the learners. The findings shows that, there are both advantages and disadvantages in using Google Translate for Englishlanguage learning, the advantages are learners are able to enrich their vocabulary because it provide the synonym, learners will know how to pronoun a word correctly and the disadvantages is learners may find the wrong meaning of a word.And lastly, the findings show that by using Google Translate a learner can develop their vocabulary, speaking skill, and also their grammar.